Legal Implications of Criminal Acts of Falsification of Covid-19 Rapid Test Letter by the Community - Deu, Cahyunisa Ramadhani (Universitas Negeri Gorontalo, 2024)
The definition of the crime of forgery of letters above that the crime of forgery of letters at the present time often occurs in the health order in Indonesia considering that until now Indonesia has experienced the Covid-19 pandemic outbreak that has hit all corners of the country, and the implications require the Indonesian government both central and regional to take various policies in dealing with the Covid-19 problem by issuing a Covid-19 rapid test letter as a certificate that a person's body is reactive or non-reactive in fighting Covid-19 in every person's body, the legal basis for the Decree of the Minister of Health of the Republic of Indonesia Number Hk.01.07/Menkes/247/2020 concerning Guidelines for the Prevention and Control of Coronavirus Disease 2019 (Covid-19), Minister of Health Regulation Number 1501/Menkes/Per/X/2010 concerning Certain Types of Infectious Diseases that can Cause Death. .07/Menkes/247/2020 concerning Guidelines for the Prevention and Control of Coronavirus Disease 2019 (Covid-19), Regulation of the Minister of Health Number 1501/Menkes/Per/X/2010 concerning Certain Types of Infectious Diseases that can Lead to Outbreaks and Countermeasures and high rules in Law Number 6 of 2018 concerning Health Quarantine which regulates and requires a Covid-19 rapid test certificate, rapid test letters are used by the government for everyone who travels across regions and abroad.